Christ the Living Stone - Fahey, Michael A. (Toronto journal of theology, 2000)
One of the few English-language hymns still used by both Reformation and Roman Catholic congregations since the displacement of the "standard" repertory by the new wave of liturgical hymns is the moving praise "The Church's One Foundation Is Jesus Christ Her Lord" composed by Samuel John Stone (1839-1900). The hymn draws upon a metaphor taken from the activity of building. In this vision Christians are seen as a community of believers, a house with many mansions or rooms built on a solid base or "foundation" as a protection against destabilization or destruction. In the geological setting of Palestine where earthquakes, windstorms, sandy soil and seasonal rains and floods are not unknown, it has been especially important for builders to secure a house on a solid foundation.